(untitled) - Grabowski, Ralph (Autralia, 2005)
Thoroughly updated to AutoCAD® 2005, this easy-to-understand essentials edition explains how to use all the commands required for 2D drafting of single drawings. All aspects of AutoCAD fundamentals are covered, from an introduction to computer hardware and CAD software, to learning to draw with objects, direct editing of objects, and plotting. Step-by-step tutorials make learning to use and apply AutoCAD 2005 and its commands a breeze, and will speed users to proficiency using the most current design capabilities of the software.
Keywords: Autocad,Computer graphics